The relationship between placental location and pregnancy outcome - يونس, دانيا; لؤي حسن; لينا رمضان (Latakia University Journal -Medical Sciences Series, 2022)
Objective: Determine whether the location of the placenta has a relationship with the presence of unpleasant and poor pregnancy outcomes (hypertensive disorders of pregnancy-low birth weight for gestational age-intrauterine fetal death).and to evaluate any association between the placental location and different blood groups. Patients and methods: A prospective cohort study that included 520 pregnant women with a single pregnancy investigated for inclusion criteria .Ultrasound was done for the women before birth and determining placental location (fundal-anterior-posterior-lateral),then the pregnancy outcome was documented (hypertension-newborn weight-newborn vitality).In addition to, documenting the blood group of all women in our study. The duration of the research is a full year, from February 2021 to February 2022 AD. Results: The women age was 26.3 ± 5.1 . A total 520 case notes of women were analysed for placental location, pregnancy outcome and blood groups. Lateral placenta was found to have a relation with a greater risk of hypertensive disorders of pregnancy (HDP) (p=0.045) , and low birth weight for gestational age (SGA) (p=0.042). While there is no relation between placental location and intrauterine fetal death (p=0.569), and the blood groups (p=0.158). Conclusion: Lateral placenta implantation is associated with an increased risk of hypertensive disorders of pregnancy and low birth weight for gestational age, while the placental location is not associated with intrauterine fetal death and the blood groups.